DIAMOND+MEGAN: Fast and Easy Taxonomic and Functional Analysis of Short and Long Microbiome Sequences. Issue 3 (3rd March 2021) - Bağcı, Caner; Patz, Sascha; Huson, Daniel H.
Abstract: One main approach to computational analysis of microbiome sequences is to first align against a reference database of annotated protein sequences (NCBI‐nr) and then perform taxonomic and functional binning of the sequences based on the resulting alignments. For both short and long reads (or assembled contigs), alignment is performed using DIAMOND, whereas taxonomic and functional binning, followed by inter‐ active exploration and analysis, is performed using MEGAN. We provide two step‐by‐step descriptions of this approach: © 2021 The Authors. Basic Protocol 1 : Taxonomic and functional analysis of short read microbiome sequences Support Protocol 1 : Preprocessing Basic Protocol 2 : taxonomic and functional analysis of assembled long read microbiome sequences Support Protocol 2 : Taxonomic binning and CheckM